Analysis of the Influence of Bank BRI Ultra Mikro Holding, Pegadaian, and PNM on Net Profit - Dwi Afriyanti, Erlisa Anggraini; Sari, Linda Karlina; Gustari, Irvandi (Indonesian Journal of Multidisciplinary Science, 2025)
This research examines the impact of the formation of ultra-micro state-owned enterprise (SOE) holdings, consisting of Bank Rakyat Indonesia (BRI), Pegadaian, and PT Permodalan Nasional Madani (PNM), on the financial performance of these entities, particularly their net profit. Indonesia’s ultra-micro businesses face significant challenges such as limited access to funding and high borrowing costs, which this holding aims to address by fostering synergies between the institutions. The research utilizes a quantitative approach with panel regression analysis to evaluate the relationship between cost efficiency, customer growth, net profit, and integration risk over time. The findings indicate that the formation of the ultra-micro holding led to significant improvements in net profit, with a notable shift in the factors influencing profitability. Before the holding, deposits were the dominant factor affecting profits; after the formation, the number of customers became the most significant variable, reflecting the increased reach and financial inclusion brought about by the integration. This synergy has also resulted in improved operational efficiency and a reduction in the cost of funds. The study suggests that continued digital integration, product development, and human resource capacity building are essential to sustaining the holding's success.